Changes of antioxidants following powdery mildew infection of near-isogenic barley lines carrying different resistance genes - Harrach, Borbála Dorottya; Fodor, József; Barna, Balázs (Acta Biologica Szegediensis, 2005)
Activities of several antioxidative enzymes (SOD, APX, GST and POX) were enhanced in barley leaves following powdery mildew infection, most significantly in case of the susceptible cultivar. In three different powdery mildew resistant lines (carrying Mla, Mlg or mlo resistance genes) we detected similar changes, but less pronounced as compared to the susceptible variety. CAT activity did not change significantly. DHAR activity decreased in all powdery mildew infected barley lines. Ascorbate and glutathione levels increased in the susceptible variety.